2023
DOI: 10.3390/e25101399
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Fast Image Encryption Algorithm Based on Three-Dimensional Chaotic System

Yiming Wang,
Xiangxin Leng,
Chenkai Zhang
et al.

Abstract: This paper introduces a novel three-dimensional chaotic system that exhibits diverse dynamic behaviors as parameters vary, including phase trajectory offset behaviors and expansion–contraction phenomena. This model encompasses a broad chaotic range and proves suitable for integration within image encryption. Building upon this chaotic system, the study devised a fast image encryption algorithm with an adaptive mechanism, capable of autonomously determining optimal encryption strategies to enhance algorithm sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Table 5 displays entropy values for the examined images, compared to those of various existing encryption methods. The results indicate that the entropy values are consistently equal to or greater than 7.996, similar to the study of Khan et al [25], and outperforming values reported by several researchers [23,[33][34][35].…”
Section: S(m C)supporting
confidence: 88%
See 1 more Smart Citation
“…Table 5 displays entropy values for the examined images, compared to those of various existing encryption methods. The results indicate that the entropy values are consistently equal to or greater than 7.996, similar to the study of Khan et al [25], and outperforming values reported by several researchers [23,[33][34][35].…”
Section: S(m C)supporting
confidence: 88%
“…Recently, Chen et al [32] developed an enhanced digital image ciphering method using a collage model and a one-dimensional quadratic chaotic system, thus expanding the key space that offers robust resilience against exhaustive attacks. Wang et al [33] proposed an improved 3D chaotic system characterized by various dynamic behaviors, such as phase shifts and expansion and contraction phenomena that vary with parameter changes. The proposed model covers a wide chaotic range and demonstrates its applicability in image encryption processes.…”
Section: Related Workmentioning
confidence: 99%
“…This implies that preprocessing of the user-inputted key for image encryption is necessary to generate a more intricate form, such as a pseudorandom sequence [23]. However, these keys can be altered by simple operations like rearranging the image stream [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Li Jian et al proposed a semiconductor 32 image encryption method based on a smooth memristor with a conservative memristor chaotic system, which provided a reference for further research on the application of conservative memristor chaotic systems in the field of image encryption [23]. In 2023, Wang Yiming et al designed a fast image encryption algorithm with an adaptive mechanism based on a 3D chaotic system [24]. The above research is limited to the encryption of a chaotic system with fixed parameters, the key space is insufficient, the complexity is low, it is easy to be affected by the short period and chaotic degradation and the security is poor as the same key flow is used for each image.…”
Section: Introductionmentioning
confidence: 99%